الإرتقاء بجودة التعليم المعماري من خلال ضبط تعليم البرامج الحاسوبية الداعمة - الأحمر, جمال; سرحان, هنادي (Latakia University Journal -Engineering Sciences Series, 2019)
The quality of architectural education is very much related to providing societies with highly qualified staffs' enriched with knowledge and skill. These design supporting soft wares have become so popular in architecture. Furthermore, the International Society for Technology in Education ISTE*** has confirmed the integrating of technology into education. What is more many of the architectural education programs have added courses of supporting programs learning, and combining the traditional and digital methods in studying architectural designs courses. This research paper discuses methods for using design supporting programs in architectural education, It also looks for ways to classify integration methods in line with local and international experiences. This study shows how students use these supporting programs and examines their ability to employ their potential in architectural design process. This could be achieved by analyzing sample of local graduation projects that aim at exploring the possible effect of these programs on the outcomes of the architectural programs courses. It also conducts an questionnaire for a sample of architecture students to measure their skill and how to acquire and use it in architectural design process. The results showed (from student perspective) that these programs are used for visual presentation without making a good use of them in primal designing stage. This in turn, had an undesirable impact on the quality of the educational outputs. يرتبط مفهوم جودة التعليم المعماري بتخريج كوادر تمتلك المعرفة و المهارة التي تمكنها من مزاولة المهنة ، وقد أخذت البرامج الحاسوبية الداعمة للتصميم دوراً واسعاً في مجال الهندسة المعمارية . و أكدت الجمعية الدولية للتكنولوجيا في التعليم ISTE *** على دمج التكنولوجيا في العملية التعليمية ، وقامت العديد من برامج التعليم المعماري بإضافة مقررات تعليم استخدام البرامج الداعمة فيها ، و الجمع بين الأساليب التقليدية والرقمية في دراسة مقررات التصميم المعماري. تناقش هذه الورقة أساليب استخدام البرامج الحاسوبية الداعمة للتصميم في التعليم المعماري ، و يتناول البحث لتصنيف طرق دمجها فيه وفق تجارب عالمية، وأخرى محلية، تعرض هذه الدراسة طريقة استخدام الطلاب للبرامج الداعمة وتلمس مدى قدرة الطلاب على توظيف إمكانياتها في مراحل عملية التصميم المعماري ، من خلال تحليل عينة من مشاريع التخرج لعدد من برامج التعليم المعماري المحلية و الهدف منها استكشاف التاثير المحتمل للبرامج على سوية منتج مقررات التصميم المعماري . وكذلك اجراء استبيان لعينة من طلاب الهندسة المعمارية لقياس مستوى المهارة لديهم وطريقة اكتسابها وكيفية توظيفها في مراحل العملية التصميمية ، وأظهرت النتائج من منظور الطلاب استخدام البرامج للإظهار البصري دون الاستفادة منها في عملية التصميم ومراحلها المبكرة وهذا ما كان له إنعكاس غير مرغوب فيه على جودة المخرجات التعليمية.